TESTING OF THE TRUTH IN ANDREI PLATONOV’S TALE THE FOUNDATION PIT - Marina Vladimirovna Zavarkina (Проблемы исторической поэтики, 2014)
Analyzing the manuscript of Andrei Platonov’s tale The Foundation Pit and his early journalism the author traces the evolution of Platonov’s views on the problem of the search for the truth. Analysis of the dynamic transcription of the The Foundation Pit manuscript enabled to show that by the end of the 1920s Platonov had abandoned rationalistic interpretations of the concept of «truth», including in its "Bogdanov’s edition". Platonov increasingly questioned the capabilities of socialist science, based on materialism, to fi nd out the truth about the world, and changed his views on work as the only method of learning the truth. He departed from the materialistic concept of learning and shifted towards the religious and philosophical tradition: in the end the formula of P. Florensky "truth-estina (to be in existence)" is getting more and more essential and it is outlined a shift of the concept of “truth” from a cognitive-materialistic category (“invent” / “to do” truth) to an ontological and moral category.